The Ruins of Nostalgia - Sankaran, T. (Book collections on Project MUSE., 2023)
"An insider's eight-decade overview of South India's 20th century classical music culture. This book offers an account of Carnatic music culture drawing on the knowledge of T. Sankaran, a musician raised in an illustrious non-Brahmin devadasi family, and his long affiliation with cultural institutions including All India Radio (AIR) and the Tamil Isai Sangam (Tamil Music Academy). Sankaran examines the cultural and social matrix in which Carnatic music was cultivated and consumed in mid-twentieth century India, including the ways that musicians negotiated caste politics and the double standard for male and female musicians. The memoir provides insight into the way AIR worked as a modern, bureaucratic institution, and how the opening of government music colleges interacted with caste politics and the shifted womens' participation in public performance. The book is polyvocal, as Sankaran's writing is interwoven with passages from Daniel M. Neuman's book The Life of Music in North India, which inspired Sankaran's project, as well as transcripts from interviews with Sankaran by Matthew Allen. Includes rare archival photos"--